ANALISIS FORMULASI KEBIJAKAN KLASTER KERJA PADA DIREKTORAT JENDERAL BEA DAN CUKAI - Setia Handaya; Tri Rahmini Siwi Utami; Lala Romlah (Prosiding SEMANIS: Seminar Manajemen Bisnis, 2023)
One of the policies in managing Human Resources within the Ministry of Finance, as set forth in the Minister of Finance Regulation number 77/PMK.01/2022 concerning the Ministry of Finance's Strategic Plan for 2020-2024 is a minus growth policy. The work zone concept has previously been implemented within the Directorate General of Customs and Excise in the form of a work area as stipulated in the Director General Regulation Number PER-31/BC/2014 concerning Transfer Patterns of Echelon IV and Echelon V Structural Positions as well as Skilled Level and Expert Level Functional Positions (First Expert Level and Second Expert Level) within the Directorate General of Customs and Excise. The division of work clusters within the Directorate General of Customs and Excise is structured according to the principle of agglomeration of geographical or territorial locations. Broadly speaking, there are 8 major islands in Indonesia, namely Sumatra, Java, Kalimantan, Sulawesi, Bali, Nusa Tenggara, Maluku and Papua. From this agglomeration, a work cluster was created at the Directorate General of Customs and Excise.